2016
DOI: 10.1002/ange.201510844
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Inorganic Nanovector: Passive versus Active Tumor Targeting in siRNA Transportation

Abstract: Seoul 133-791 (Republic of Korea) Supportinginformation for this article can be found under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Selective tumor targeting and siRNAbased mRNA degradation in vitro and in vivo [119] MgAl Ovalbumin (antigen) and CpG (ligand)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective tumor targeting and siRNAbased mRNA degradation in vitro and in vivo [119] MgAl Ovalbumin (antigen) and CpG (ligand)…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Choy's group is exploring theranostic siRNA-LDH nanohybrids system for targeted cancer therapy and imaging function (Fig. 17) [119]. Two groups of siRNA-LDH nanohybrids were developed for the in vivo delivery of siRNA with advanced cancer treatment.…”
Section: Gene-ldh Theranostics In Vitro and In Vivomentioning
confidence: 99%
“…The accumulation of TiS 2 -HSA-FA in tumor was likely due to the FA modification, which is known to facilitate tumor targeting. 44,45 As shown in Figure 5C, after intravenous injection, blood distribution half-life (t 1/2 α) and blood terminal elimination half-life (t 1/2 β) of the TiS 2 -HSA-FA were 1.21±0.11 hrs and 17.52±0.62 hrs, respectively. It has been reported that PEG and HSA modifications can prolong blood circulation and reduce macrophage clearance of nanoparticles from the reticuloendothelial system.…”
Section: In Vivo Biodistribution and Blood Circulationmentioning
confidence: 94%
“…Recent progress in ceramic nanosystems has led to innovations in fields combining biomedicine, energy, the environment, and even information technology. [3][4][5][6][7][8][9] In recent decades, globalization has evolved at an exponential pace due to the digital revolution and rapid advances in various technologies that have led to an increase in the quantity of digital information. 10) As a result, the requirement of a code system has emerged that can carry a high density of information and allows reliability, integrity, authenticity, and confidentiality in data processing.…”
Section: Introductionmentioning
confidence: 99%